A Note on the Strong Law of Large Numbers for Arrays of Rowwise ρ˜-Mixing Random Variables - Aiting Shen; Shuhe Hu (Discrete Dynamics in Nature and Society)
Let {Xni,i≥1,n≥1} be an array of rowwise ρ˜-mixing random variables. Some strong law of large numbers for arrays of rowwise ρ˜-mixing random variables is studied under some simple and weak conditions.